Innovative performance of EU member states - Vlatka, Bilas; Bošnjak, Mile; Novak, Ivan (Oeconomica Jadertina, 2019)
The aim of this paper is to show the results of the innovation performance of the member states of the European Union. The most comprehensive insight into the innovation performance of countries is provided by the Global Index of Innovation, the Bloomberg Index of Innovation and the European Innovation Success Scale. These indices have different methodologies for calculating innovation performance of countries, and depending on the type of country index and methodology they produce different results. Comparative analysis of the innovation index has shown that, depending on the type of index and methodology of calculation, the leading countries of the world are Switzerland and South Korea, and the most innovative countries of the European Union are Sweden and the Netherlands. Nevertheless, according to all three indices and methodologies some European Union member states show weak innovation performance, such as Croatia, Bulgaria and Romania. The comparative analysis of the indices in question points to the weakest links of the economy that needs to be strengthened in order to improve the level of innovation and, consequently, competitiveness, which is why the listed results represent guiding and defining principles, guideline priorities and innovation policies measures.
Keywords: Innovation performance; Innovation; Global Index of Innovation; Bloomberg Innovation Index; European Innovation Success Scale